A BRIEF SURVEY ON FINITE TIME AND FIXED TIME SYNCHRONIZATION OF COMPLEX DYNAMICAL NETWORKS AND ITS APPLICATIONS. (2020) - ANAND, K.S.; PADMANABHAN, S.; BABU, G.A. HARISH; BRINDA, R.
No abstract available